The right of citizens to appeal to state authorities in the information society: experience of the Republic of Belarus and foreign states - Haurylenka, Anton V.; Fedarovich, Aliaksei V. (Journal of the Belarusian State University. International Relations, 2020)
We consider that new digital solutions used to improve the mechanism for ensuring the right of citizens to appeal to state organs. Based on the analysis of legal acts and law application practice of a number of foreign states, the authors propose to consolidate in national legislation such form of appeal as an electronic petition. The article shows the problematic points that arise in connection with the introduction of modern technologies in working with citizensʼ appeals, affecting the protection of personal data, abuse of law, etc. A set of organizational and legal measures to overcome such problems, including creation and successful operation of a unified information system for recording and processing applications from citizens and legal entities are proposed by authors.
Keywords: the right to appeal; human rights; e-petition; e-government; public administration